Evaluation of myocardial function in patients with rheumatoid arthritis using strain imaging by speckle-tracking echocardiography - Fine, Nowell M; Crowson, Cynthia S; Lin, Grace; Oh, Jae K; Villarraga, Hector R; Gabriel, Sherine E (Annals of the rheumatic diseases, 2014)
Objectives Patients with rheumatoid arthritis (RA) are at increased risk for cardiovascular disease (CVD), although strategies to detect subclinical CVD are poorly characterised. The purpose of this study was to assess myocardial function by speckle-tracking echocardiography strain imaging in patients with RA without known CVD. Methods Eighty-seven patients with RA selected from a population-based sample underwent echocardiography. Left ventricular (LV) and right ventricular (RV) longitudinal peak systolic strain were measured. A subset of 59 patients with RA was compared with 59 age-, gender- and race-matched subjects with normal echocardiography and no CVD or risk factors. Results The mean ± SD age of the patients with RA and the normal patients was 55.7±12.1 and 54.5±12.2 years (p=0.42), respectively, with 45 (76%) women in each group. Global LV strain (−15.7±3.2% vs −18.1±2.4%, p<0.001) and RV strain (−17.9±4.7% vs −20.7±2.4%, p<0.001) was reduced in patients with RA compared with normal patients. Among all 87 patients with RA the mean disease duration and C-reactive protein at echocardiography were 10.0±6.1 years and 3.5±3.7 mg/L, and 74% were seropositive. Adjusted univariate regression analysis demonstrated a significant correlation between global LV strain and RA Health Assessment Questionnaire disability index (p=0.032), and borderline associations with prior use of oral corticosteroids (p=0.062) and methotrexate (p=0.054) after adjustment for age, gender, blood pressure, body mass index, heart rate and LV mass index. Conclusions Global longitudinal LV and RV strain is reduced in patients with RA compared with healthy patients. Strain abnormalities correlate with RA disease severity. Strain imaging by echocardiography may detect early myocardial dysfunction in RA.